Tensions in Anglican – Roman Catholic Dialogue Doctrinal and Moral Absolutes 1980–2020 - Sedgwick, Peter H. 1948- (2021)
Abstract The article surveys Anglican – Roman Catholic ecumenical relationships from 1980–2020. It examines the belief in doctrinal and moral absolutes in official statements of the cdf , and the impact this had on documents from arcic . This was different from statements from the pcpcu , especially in relationship to wcc texts. The article concludes by looking at the changes since the election of Pope Francis, and whether ecumenical relationships will be different in the future.
Keywords: Historicism; moral absolutes; Roman Catholicism; Anglicanism; Ecumenism